2019
DOI: 10.1111/1754-9485.12964
|View full text |Cite|
|
Sign up to set email alerts
|

Adoption of hypofractionated radiation therapy for early breast cancer in private practice: the GenesisCare experience 2014–2106

Abstract: Introduction: Cancer Australia guidelines recommend that hypofractionation should be considered for women over the age of 50 years with early breast cancer. GenesisCare is the largest provider of radiation therapy services in Australia. This study aimed to investigate variation in hypofractionation across 4 states encompassing the period when the most recent guidelines had been released. Methods: Patients with T1 N0 and T2 N0 breast cancer who received radiation therapy as adjuvant therapy after breast conserv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
1
2
1
Order By: Relevance
“…Our study identified that the residence LHD influenced the use of hypofractionation reflecting variation between facilities, and previous studies have identified prescribing radiation oncologist as a factor [9] , [12] , [24] . Prades et al [24] suggested two reasons for understanding clinicians’ reluctance to adopt hypofractionation regimens; (1) some clinicians perceived newer treatment techniques as ‘another layer of complexity’ that seemed to slow adoption of hypofractionation, (2) quality of evidence is a necessary but not a sufficient condition determining clinician’s behaviour towards hypofractionation including clinical management factors, such as the role of the department head.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…Our study identified that the residence LHD influenced the use of hypofractionation reflecting variation between facilities, and previous studies have identified prescribing radiation oncologist as a factor [9] , [12] , [24] . Prades et al [24] suggested two reasons for understanding clinicians’ reluctance to adopt hypofractionation regimens; (1) some clinicians perceived newer treatment techniques as ‘another layer of complexity’ that seemed to slow adoption of hypofractionation, (2) quality of evidence is a necessary but not a sufficient condition determining clinician’s behaviour towards hypofractionation including clinical management factors, such as the role of the department head.…”
Section: Discussionsupporting
confidence: 61%
“…Previous studies in NSW have also identified age, laterality, year, and treating facility as factors that correlated significantly with hypofractionation use in patients with early breast cancer [9,12]. Although our study and previous published studies [8,9,12] showed increase in hypofractionation use over time, this rate of increase is very slow.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations